Disseminating the CERDAS Model to Strengthen Character-Based Tax Literacy among Teachers - Ismail, Ismail; Rahmat, Rahmat; Gunawan, Arung; Aida Rais, Fitri (Maspul Journal of Community Empowerment (MJCE), 2026)
Tax literacy plays an important role in fostering responsible citizenship from an early age; however, its implementation in primary schools remains limited due to teachers’ insufficient competencies and the lack of structured instructional models. This community service program aimed to disseminate the CERDAS Model (Observe–Explore–Reflect–Discuss–Act–Realize) to strengthen character-based tax literacy among teachers at MI Muhammadiyah Buntu Barana, Enrekang Regency. The program adopted a community empowerment approach consisting of needs assessment, model dissemination, instructional material development workshops, classroom mentoring, and monitoring and evaluation. The results demonstrated improvements in teachers’ competencies in understanding tax literacy concepts, developing teaching modules, designing learning media, and implementing the CERDAS Model in classroom instruction. The program also produced teaching modules, student worksheets, interactive learning media, assessment instruments, and established a Tax Literacy Teacher Community to support program sustainability. These outcomes indicate that the program successfully strengthened teachers’ capacities while translating research findings into innovative, contextual, and sustainable classroom practices in primary education.